Hubungan Antara Kematangan Emosi dan Iklim Organisasi Dengan Prokrastinasi Kerja Karyawan PT. Surya Madistrindo Area Office Medan - Lukas Fernando; Sjahril Effendy; Risydah Fadilah (Tabularasa: Jurnal Ilmiah Magister Psikologi, 2021)
This study aims to determine empirically the relationship between emotional maturity and organizational climate with the employee work procrastination of PT. Surya Madistrindo Area Office Medan. The population in this study were 315 people. This study used purposive sampling technique amounted to 60 people. This research uses a quantitative approach. The instrument used was a valid and reliable questionnaire for emotional maturity, organizational climate and work procrastination. This study was analyzed by means of multiple regression analysis. The results showed that: (1) There is a negative relationship between emotional maturity and work procrastination seen from the coefficient (Rx1y) = -0.609 with p 0.000 0.050. The contribution of emotional maturity to work procrastination can be seen from the coefficient of determination (R2) = 0.371 or 37.1%. (2) There is a negative relationship between organizational climate and work procrastination which is coefficient (Rx2y) = -0.465 with p = 0.000 0.050. The contribution of emotional maturity to work procrastination can be seen from the coefficient of determination (R2) = 0.216 or 21.6%. (3). There is a negative relationship between emotional maturity and organizational climate with work procrastination seen from the coefficient value (Rx1x2y) = -0.637 with p = 0.000 0.050. The contribution of emotional maturity and organizational climate to work procrastination is seen from the value of the coefficient of determination (R2) = 0.406 or 40.6%.